(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
The aim of this article is to introduce the German dialect Mòcheno, a minority languagespoken in Trentino (Italy). By analysing the syntax of the direct object in main and interrogative clauses, the syntax of subject pronouns and by comparing Mòcheno with older Germanic languages, I show that the variation displayed by this language, which is completely absent from both German and its dialects, is not a consequence of direct syntactic borrowing from the contact Romance varieties, as previously thought, but emerges from one single and autonomous grammar. KEYWORDS: OV/VO, subject pronouns, syntax of NP subjects, older Germanic, double-base hypothesis